High potential of magnet on the performance of dual piezoelectric fans in electronics cooling system - Fadhilah, Abdul Razak (Institute of Advanced Engineering and Science, 2018)
Recently, piezoelectric fan has gained attention as potential active cooling method for electronics devices. Even though the piezoelectric requires high voltage, there are findings to overcome the shortcomings. Adding on a magnet at the tip of the piezoelectric fan to activate other magnetic passive fans is one of the methods to increase the total amplitude generated by the fans. This paper will discuss on the performance of integrated piezoelectric fan with passive fans (later refer to magnetic fans) to enhance the heat transfer in cooling system. A repulsive force produced by the magnets will cause the magnetic blades to oscillate together with the piezoelectric fan. The paper will focus on the optimization parameters of the magnets for selected dimension of piezoelectric fan. The parameters under investigation are the position of the magnet on the piezoelectric fan, number of magnets on each blades and orientation of blades with respect to adjacent blade. Results show that the magnet at middle location of extensive blade with double magnets generate the largest amplitude, 80% better than fan without magnet and for dual integrated piezoelectric fan with magnetic fan, radial orientation gives better result by 25%. By increasing the total amplitude using magnetic force, power consumption can be reduced while the heat transfer performance can be enhanced. it shows a good agreement for positive heat transfer and thermal resistance improvement compared to natural convection.